Long-Term Outcome of Centrally Located Hepatocellular Carcinomas Treated by Radical Resection Combined With Intraoperative Electron Radiotherapy (IOERT) - Wu, Yan-Ling; Zhai, Yirui; Li, Minghui; Cai, Jian-Qiang; Ma, Pan; Wang, Li-Ming; Wu, Xiu-Hong; Wang, Xiao-dan; Wu, Fan; Zeng, Qiang; Chen, Bo; Li, Ye-Xiong; et al. (Frontiers in Oncology, 2022)
Purpose: To explore the feasibility and safety of centrally located hepatocellular carcinoma (CL-HCC) treated by narrow-margin resection combined with intraoperative electron radiotherapy (IOERT). Methods and Materials: From November 2009 to November 2016, 37 consecutive patients were treated with IOERT as adjuvant treatment during narrow-margin resection for CL-HCC. Long-term outcomes, adverse events for surgery, and acute and chronic toxicities were analyzed. Results: The median follow-up was 57.82 months (range, 3.75-111.41 months). A total dose of 15 Gy (range 12 to 17Gy) (prescribed at the 90% isodose) was delivered with a 0.9cm (range 0.8-1.2 cm) median treatment depth targeting the narrow-margin. The 1-year, 3-year and 5-year OS rates were 91.39%, 88.34% and 88.34%, respectively. The 1-year, 3-year and 5-year DFS rates were 80.81%, 68.59% and 54.17%, respectively. In the univariate analysis, none of the treatment characteristics were predictive of overall survival. Fifteen (40.5%) patients suffered from a recurrence event. No patient had marginal recurrence. The 1-year, 3-year and 5-year intrahepatic recurrence rates were 19.75%, 25.92% and 39.58%, respectively. The 1-year, 3-year and 5-year extrahepatic recurrence rates were 2.7%, 5.95% and 9.87%, respectively. There was no 30-day surgical-related death. Three patients had grade 4, and 28 patients had grade 3 alanine aminotransferase (ALT) levels, and seven patients had grade 4, and 30 patients had grade 3 aspartate transaminase (AST) levels. All of them returned to normal within four months. There was no acute radiation-induced liver injury during follow-up. There were no acute or chronic toxicities associated with IOERT. Conclusion: IOERT for narrow-margin CL-HCC may achieve good long-term survival outcomes, without significantly increasing acute and chronic toxicities. An IOERT dose of 15Gy may be the safest and most feasible. IOERT might be considered as an adjuvant therapy for CL-HCC patients with a narrow-margin.